Sanctions of the Notary Supervisory Board of Banten Province Against Notaries Who Do Not Provide Services in Accordance with the Notary Law - Febrianto, Rohman Dwi (Sultan Agung Notary Law Review, 2024)
This Notary Code of Ethics contains various matters related to the duties and authorities of Notaries in carrying out their profession and position as public officials. The material elements contained in this Notary Code of Ethics include obligations, prohibitions, exceptions and sanctions that will be imposed on Notaries who violate this Code of Ethics.This study aims to determine and analyze:1) To find out and analyze what kind of Notary can be said not to provide services in accordance with the provisions of the Notary Law; 2) To find out and analyze the form of Sanctions imposed by the Notary Regional Supervisory Board in Banten Province; and 3) To find out and analyze the basis for consideration of the Banten Province Regional Supervisory Board in imposing sanctions. The conclusion of the research results of the Banten Province Regional Supervisory Board imposes Sanctions on Notaries who Do Not Provide Services in Accordance with the Provisions of the Notary Law, the Notary Supervisory Board can impose sanctions on violators, the sanctions imposed on members of the Indonesian Notary Association who violate the code of ethics can be: Reprimand, Warning, Schorzing (temporary dismissal) from members of the association, Onzetting (dismissal) from members of the association, and Dishonorable Dismissal from members of the association. However, the dismissal sanction given to Notaries who violate the code of ethics is not in the form of dismissal from the notary position but dismissal from membership of the Indonesian Notary Association.